1988
DOI: 10.1007/bf00003034
|View full text |Cite
|
Sign up to set email alerts
|

Sources, fates, and impacts of nitrogen inputs to terrestrial ecosystems: review and synthesis

Abstract: Abstract. The relative importance of nitrogen inputs from atmospheric deposition and biological fixation is reviewed in a number of diverse, non-agricultural terrestrial ecosystems. Bulk precipitation inputs of N (I-12kgN ha-' yr-') are the same order of magnitude as, or frequently larger than, the usual range of inputs from nonsymbiotic fixation (< 1 -5 kg N ha-' yr-I), especially in areas influenced by industrial activity. Bulk precipitation measurements may underestimate total atmospheric deposition by 3040… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(84 citation statements)
references
References 133 publications
1
81
0
1
Order By: Relevance
“…Using 1996 vegetation data obtained from the Coastal Landscape Analysis and Modeling Study (http://www.fsl.orst.edu/ clams), we estimate that about 23% of the Yaquina Watershed is vegetated with red alder (assuming that the broadleaf cover is primarily alder). Using published N fixation rates of 50-200 kg N ha −1 year −1 (Boring et al 1988;and Binkley et al 1994) and the coverage of alder in the Yaquina watershed, we estimate that >98% of the annual riverine N loading to Yaquina Bay may be related to the presence of red alder in the watershed. Compton et al (2003) found a relationship between broadleaf and mixed cover and annual N export (N export , kg N ha −1 year −1 ) in the Salmon River basin…”
Section: Watershed Inputsmentioning
confidence: 92%
“…Using 1996 vegetation data obtained from the Coastal Landscape Analysis and Modeling Study (http://www.fsl.orst.edu/ clams), we estimate that about 23% of the Yaquina Watershed is vegetated with red alder (assuming that the broadleaf cover is primarily alder). Using published N fixation rates of 50-200 kg N ha −1 year −1 (Boring et al 1988;and Binkley et al 1994) and the coverage of alder in the Yaquina watershed, we estimate that >98% of the annual riverine N loading to Yaquina Bay may be related to the presence of red alder in the watershed. Compton et al (2003) found a relationship between broadleaf and mixed cover and annual N export (N export , kg N ha −1 year −1 ) in the Salmon River basin…”
Section: Watershed Inputsmentioning
confidence: 92%
“…However, most terrestrial ecosystems are nitrogen limited (Vitousek and Howarth 1991) and may not respond to elevated CO 2 with increased plant growth unless there is a concomitant increase in nitrogen availability (Kramer 1981). Biological N 2 -fixation currently accounts for 60% of the "new" nitrogen deposited on land annually (Schlesinger 1991) and symbiotic N 2 -fixing trees may be expected to improve the fertility of N-deficient soils in a high CO 2 environment by gradually increasing soil N content (Boring et al 1988;Chapin et al 1994). Thus, N 2 -fixing trees may stimulate photosynthesis and growth under elevated CO 2 conditions, inducing positive feedback on rates of carbon sequestration in forests.…”
Section: Introductionmentioning
confidence: 99%
“…Allocation may also change over time as the availability of N changes, as may the C:N ratios of the plant tissue (Boring et al 1988, Vitousek et al 1988). These simulations suggest that net C uptake is likely to be more sensitive to any changes in allocation than to C:N ratio changes within each tissue type.…”
Section: Resultsmentioning
confidence: 99%